2013
DOI: 10.1104/pp.113.218156
|View full text |Cite
|
Sign up to set email alerts
|

Export of Salicylic Acid from the Chloroplast Requires the Multidrug and Toxin Extrusion-Like Transporter EDS5    

Abstract: Salicylic acid (SA) is central for the defense of plants to pathogens and abiotic stress. SA is synthesized in chloroplasts from chorismic acid by an isochorismate synthase (ICS1); SA biosynthesis is negatively regulated by autoinhibitory feedback at ICS1. Genetic studies indicated that the multidrug and toxin extrusion transporter ENHANCED DISEASE SUSCEPTIBILITY5 (EDS5) of Arabidopsis (Arabidopsis thaliana) is necessary for SA accumulation after biotic and abiotic stress, but so far it is not understood how E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
165
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(174 citation statements)
references
References 31 publications
2
165
0
2
Order By: Relevance
“…This response not only becomes apparent in the ICS1-defective sid2 plants, but also in another SA induction-deficient mutant, sid1, which bears a defect in the multidrug and toxin extrusion-like transporter ENHANCED DISEASE SUSCEPTIBILITY5 (EDS5) ( Figure 2C). EDS5 is required for the export of chloroplast-synthesized SA from this organelle, and SA accumulation in sid1/eds5 is supposedly inhibited by autoinhibitory feedback (Serrano et al, 2013). Furthermore, the partial SAR response is established in ics1 ics2, in which both isochorismate synthase isoforms of Col-0 are inactive (Supplemental Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…This response not only becomes apparent in the ICS1-defective sid2 plants, but also in another SA induction-deficient mutant, sid1, which bears a defect in the multidrug and toxin extrusion-like transporter ENHANCED DISEASE SUSCEPTIBILITY5 (EDS5) ( Figure 2C). EDS5 is required for the export of chloroplast-synthesized SA from this organelle, and SA accumulation in sid1/eds5 is supposedly inhibited by autoinhibitory feedback (Serrano et al, 2013). Furthermore, the partial SAR response is established in ics1 ics2, in which both isochorismate synthase isoforms of Col-0 are inactive (Supplemental Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the Enhanced Disease 97 Susceptibility 5 (EDS5) SA transporter in the chloroplast envelope of Arabidopsis is 98 necessary for stress-induced SA accumulation, possibly due to a regulatory coupling of SA 99 transport and synthesis (Serrano et al, 2013;Yamasaki et al, 2013). Recently, a catabolic 100 enzyme that converts SA to 2,3 dihydroxybenzoic acid in Arabidopsis was described 101 (Zhang et al, 2013).…”
Section: In Arabidopsis 83mentioning
confidence: 99%
“…ICS1 transcript and SA levels are induced by UV-C stress in Arabidopsis (Garcion 169 et al, 2008;Martínez et al, 2004;Nawrath et al, 2002;Serrano et al, 2013;Shapiro and 170 …”
Section: Ics1 Protein Levels Are Uv-c Inducible 168mentioning
confidence: 99%
“…In contrast, overexpression of AtEDS5 in Arabidopsis enhanced SA accumulation and resistance to viruses (Ishihara et al 2008). Recent genetic and biochemical analyses showed that this MATE transporter functioned in epidermal cells by exporting SA from its site of biosynthesis in the chloroplast to the cytosol (Serrano et al 2013;Yamasaki et al 2013). This intracellular SA transport by AtEDS5, leading to SA accumulation, plays an essential role in plant innate immune signaling and in disease resistance.…”
Section: Plant Hormone Signalingmentioning
confidence: 99%